PROFIL STRATEGI PEMBELAJARAN KONTROVERSI PADA PELATIHAN GURU IPA SMPN 2 BAROMBONG - Sudarto, Sudarto; Rukayah, Rukayah; Muliadi, Muliadi; Sitti Jauhar,; Abd. Kadir, (JURNAL PENGABDIAN MANDIRI, 2025)
Education is the most priority vehicle for all of Indonesian people in improving the quality of life and living. Therefore, education is the backbone of the progress of the Indonesian nation. All efforts are made to support this field so that its function can be realized. In the field of education, there are several urgent problems to be solved. One of them is the problem of teachers in making students creative in class. This also happened at SMPN 2 Barombong where the special science teachers did not know the right and effective way to improve the student creativity. To overcome this problem, training was conducted on how to make the students creative through controversial learning strategies. In this training, teachers expect a profile or guideline on how to make the students creative through controversial learning strategies. Finally, a profile or guideline is obtained on how to make the students creative in science learning through a controversial learning strategy consisting of 5 steps, namely: (1) the teacher presents the science material or themes or science questions that contain controversial issues, (2) the teacher invites/asks the students to share their answers/opinions accompanied by arguments regarding the issues (themes or questions) that have been presented, (3) the group students where the students who have similar/the same answers/opinions are included in the same group, (4) the controversial themes/issues/questions that have been identified and answered are then discussed, and (5) the teacher and students conclude and provide the suggestions for the learning that has been carried out.